Structural Diversity of Photosystem I and Its Light-Harvesting System in Eukaryotic Algae and Plants - Bai, Tianyu; Guo, Lin; Xu, Mingyu; Tian, Lirong (Frontiers in Plant Science, 2021)
Photosystem I (PSI) is one of the most efficient photoelectric apparatus in nature, converting solar energy into condensed chemical energy with almost 100% quantum efficiency. The ability of PSI to attain such high conversion efficiency depends on the precise spatial arrangement of its protein subunits and binding cofactors. The PSI structures of oxygenic photosynthetic organisms, namely cyanobacteria, eukaryotic algae, and plants, have undergone great variation during their evolution, especially in eukaryotic algae and higher plants for which light-harvesting complexes (LHCI) developed that surround the PSI core complex. A detailed understanding of the functional and structural properties of this PSI-LHCI is not only an important foundation for understanding the evolution of photosynthetic organisms but is also useful for designing future artificial photochemical devices. Recently, the structures of such PSI-LHCI supercomplexes from red alga, green alga, diatoms, and plants were determined by X-ray crystallography and single-particle cryo-electron microscopy (cryo-EM). These findings provide new insights into the various structural adjustments of PSI, especially with respect to the diversity of peripheral antenna systems arising via evolutionary processes. Here, we review the structural details of the PSI tetramer in cyanobacteria and the PSI-LHCI and PSI-LHCI-LHCII supercomplexes from different algae and plants, and then discuss the diversity of PSI-LHCI in oxygenic photosynthesis organisms.